2002
DOI: 10.1258/095646202760326390
|View full text |Cite
|
Sign up to set email alerts
|

HIV infections in sub-Saharan Africa not explained by sexual or vertical transmission

Abstract: An expanding body of evidence challenges the conventional hypothesis that sexual transmission is responsible for more than 90% of adult HIV infections in Africa. Differences in epidemic trajectories across Africa do not correspond to differences in sexual behaviour. Studies among African couples find low rates of heterosexual transmission, as in developed countries. Many studies report HIV infections in African adults with no sexual exposure to HIV and in children with HIV-negative mothers. Unexplained high ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 79 publications
2
69
0
4
Order By: Relevance
“…Most of the reports are anecdotal, yet evidence points to a large potential transmission effect due to interactions with the health system. 15,16 The first Global Patient Safety Challenge addressed the issue of hand washing as a means of transmitting infections to patients in the hospital setting. 17 The work from this challenge resulted in guidelines aimed at improving practices of hospital staff responsible for patient care.…”
Section: Clean Surgery -Antisepsis and Control Of Contaminationmentioning
confidence: 99%
“…Most of the reports are anecdotal, yet evidence points to a large potential transmission effect due to interactions with the health system. 15,16 The first Global Patient Safety Challenge addressed the issue of hand washing as a means of transmitting infections to patients in the hospital setting. 17 The work from this challenge resulted in guidelines aimed at improving practices of hospital staff responsible for patient care.…”
Section: Clean Surgery -Antisepsis and Control Of Contaminationmentioning
confidence: 99%
“…Based on the findings of various studies, Gisselquist and colleagues 4 calculate the PAFs (causal fractions) associated with injections and conclude that, "Many studies show 20%-40% of HIV infections in African adults associated with injections (though direction of causation is unknown)". Furthermore, in analyses of data from the 1980s, Gisselquist and co-workers 3 report that, "Overall, crude PAFs from general population studies through 1988 suggest that medical exposures were responsible for more African HIV than sexual exposures".…”
Section: Population Attributable Fractions (Pafs)mentioning
confidence: 99%
“…3,4 Recently, Gisselquist and his colleagues 5 expressed skepticism that heterosexual transmission alone can explain the magnitude of sub-Saharan Africa's HIV/ AIDS pandemic. Contrary to prevailing opinions, they estimated that only 25-29% of the sub-Saharan HIV infections in women and 30-35% in men result from sexual transmission and suggested that needle exposures to HIV during health-care encounters may account for more HIV infections in sub-Saharan Africa than do sexual exposures.…”
Section: Introductionmentioning
confidence: 99%